Coldwater Periods in Warmwater Streams: Microhabitat Shifts from Autumn to Winter by Smallmouth Bass. (26th November 2019) - Wolf, Skylar L.; Mollenhauer, Robert; Brewer, Shannon K.
Abstract: Seasonal and life stage variation in microhabitat use is an important driver of fish survival and bioenergetics, but knowledge of microhabitat selection during colder periods is generally lacking in warmwater streams. Our objective was to examine changes in microhabitat selection by age‐0 (TL ≤ 85 mm) and age‐1+ (TL > 85 mm) Smallmouth Bass Micropterus dolomieu from autumn to winter in streams of the southwest Ozark Highlands ecoregion. We examined microhabitat selection (depth, velocity, substrate, cover, and temperature) during autumn 2017 (Spavinaw Creek) and winter 2018 (Spavinaw and Spring creeks). During autumn and winter, age‐0 fish selected intermediate depths of approximately 1 m, whereas age‐1+ fish selected the deepest available habitat. Water depth selection was similar across seasons for both life stages. Both age‐0 and age‐1+ bass selected areas of zero velocity, increasing substrate size, instream cover, and warmwater patches in autumn. Velocity selection differed between autumn and winter with both life stages showing stronger selection of low velocity patches (0.1–0.3 m/s) during winter. Both life stages shifted to having no substrate selection during winter. Age‐1+ bass were more likely than age‐0 bass to use cover during autumn, but this relationship shifted in winter to the age‐0 cohort increasing their selection of cover and the age‐1+ cohort decreasing their selection. Both age‐0 and age‐1+ bass selected relatively warmer habitats during autumn, but not winter. Collectively, our results highlight both seasonal and life stage variation in Smallmouth Bass microhabitat selection. As our understanding of habitat selection across seasons develops, the management of Smallmouth Bass will undoubtedly improve. Changing environmental conditions over time may influence available habitat as well as the timing of seasonal shifts across a range of spatial and temporal scales, including microhabitat patches.